Proverb as an Object of Philological Research - Ochilova, Zarifa (Indonesian Journal of Innovation Studies, 2022)
In this article, English and Uzbek folk proverbs are studied in the field of paremiology of folklore and differ from other genres of folklore with a number of peculiarities. In them, the idea is expressed in the form of a clear, complete conclusion, a concise sentence, guided by the expression of a particular sentence in a logical sequence, sharp polarity, and can be used in its own and figurative senses. In addition, the proverbs show their universal nature through the predominance of exemplary, instructive aspects.